Complete rupture of large tendons - Flik, K. R.; Bush-Joseph, C.; Bach Jr., B. R. (The Physician and Sportsmedicine, 2005)
Forceful eccentric contraction may cause a partial or complete rupture of a vulnerable large tendon, especially in middle-aged men. When diagnosing a large-tendon rupture, it is essential to rule out a systemic illness or history of local or systemic corticosteroid or anabolic steroid use, because any of these may lead to poor tendon quality and increased risk for rupture. Ultrasound or MRI may help confirm the diagnosis. Treatment is generally surgical with anatomic repair. Return to sport depends on the patient's age, lifestyle, tendon involved, and medical comorbidities.